Delivering Cost-Efficient Public Services in Health Care, Education and Housing in Chile - Moccero, Diego (OECD Economics Department Working Papers, 2008)
The Chilean authorities plan to raise budgetary allocations over the medium term for a variety of social programmes, including education, health care and housing. This incremental spending will need to be carried out in a cost-efficient manner to make sure that it yields commensurate improvements in social outcomes. Chile's health indicators show that it fares relatively well in relation to comparator countries in the OECD area and in Latin America. But this is less so in the case of education, where secondary and tertiary educational attainment remain low, despite a significant increase over the years, and performance is poor on the basis of standardised test scores, such as PISA. Even though comparison with countries in the OECD area is difficult, a sizeable housing deficit has yet to be closed in Chile. To meet these various challenges, efforts will need to be stepped up to: i) narrow the disparities in performance that currently exist among schools with students from varying backgrounds through use of the "differentiated" voucher scheme and additional measures to improve the quality of teaching and management; ii) improve risk sharing among private and public health insurers, while increasing the coverage of health insurance to a broader variety of pathologies under AUGE; and iii) continue to tackle the shortage of housing, while enhancing the quality of subsidised housing units and their surrounding neighbourhoods for the poorest segments of society. This paper relates to the 2007 Economic Survey of Chile (www.oecd.org/eco/surveys/chile)